Health and quality of life among a cohort of patients having lateral internal sphincterotomy for anal fissures. (4th July 2020) - Sutherland, J. M.; Karimuddin, A.; Liu, G.; Crump, T.; Akbar, H.; Phang, T.; Redfern, K.; Manoharan, S.; Brown, C. J.; Raval, M. J.
Abstract: Aim: The aim of this study is to report changes in health‐related quality of life attributable to lateral internal sphincterotomy for treatment of anal fissure. There is very little evidence on whether the overall health‐related quality of life of patients is detrimentally affected by the condition, or which aspects of self‐perceived health status improve after lateral internal sphincterotomy. This study will articulate which aspects of health tend to improve and guide postoperative expectations appropriately. Knowledge gained from this study may also identify gaps in an individual patient's episode of care. Method: Patients were prospectively identified when they consented to surgical treatment of their anal fissure and were contacted by phone to participate. Participants completed a number of patient‐reported outcomes preoperatively and 6 months postoperatively. Faecal incontinence‐related quality of life, pain and depression were measured at both time points. The severity of faecal incontinence was measured at both times. Results: Participants reported high levels of pain preoperatively. Postoperatively, improvement in pain exceeded the threshold of clinical relevance ( P < 0.01). Thirty‐five per cent of participants reported significant effects of faecal incontinence preoperatively, while 26% did so postoperatively. Participants with multiple comorbidities were more likely to report faecal incontinence postoperatively than preoperatively. Conclusion: This study reports that lateral internal sphincterotomy improved pain symptoms without adverse effects on continence. Not all domains of health‐related quality of life were similarly positively affected by anal fissure repair.